Conversion-to-open in laparoscopic appendectomy: A cohort analysis of risk factors and outcomes. (April 2017) - Finnerty, Brendan M.; Wu, Xian; Giambrone, Gregory P.; Gaber-Baylis, Licia K.; Zabih, Ramin; Bhat, Akshay; Zarnegar, Rasa; Pomp, Alfons; Fleischut, Peter; Afaneh, Cheguevara
Abstract: Background: Identifying risk factors for conversion from laparoscopic to open appendectomy could select patients who may benefit from primary open appendectomy. We aimed to develop a predictive scoring model for conversion from laparoscopic to open based on pre-operative patient characteristics. Methods: A retrospective review of the State Inpatient Database (2007–2011) was performed using derivation (N = 71, 617) and validation (N = 143, 235) cohorts of adults ≥ 18 years with acute appendicitis treated by laparoscopic-only (LA), conversion from laparoscopic to open (CA), or primary open (OA) appendectomy. Pre-operative variables independently associated with CA were identified and reported as odds ratios (OR) with 95% confidence intervals (CI). A weighted integer-based scoring model to predict CA was designed based on pre-operative variable ORs, and complications between operative subgroups were compared. Results: Independent predictors of CA in the derivation cohort were age ≥40 (OR 1.67; CI 1.55–1.80), male sex (OR 1.25; CI 1.17–1.34), black race (OR 1.46; CI 1.28–1.66), diabetes (OR 1.47; CI 1.31–1.65), obesity (OR 1.56; CI 1.40–1.74), and acute appendicitis with abscess or peritonitis (OR 7.00; CI 6.51–7.53). In the validation cohort, the CA predictive scoring model had an optimal cutoff score of 4 (range 0–9). The risk of conversion-to-open was ≤5% for a score <4, compared to 10–25% for a score ≥4. On composite outcomes analysis controlling for all pre-operative variables, CA had a higher likelihood of infectious/inflammatory (OR 1.44; CI 1.31–1.58), hematologic (OR 1.31; CI 1.17–1.46), and renal (OR 1.22; CI 1.06–1.39) complications compared to OA. Additionally, CA had a higher likelihood of infectious/inflammatory, respiratory, cardiovascular, hematologic, and renal complications compared to LA. Conclusions: CA patients have an unfavorable complication profile compared to OA. The predictors identified in this scoring model could help select for patients who may benefit from primary open appendectomy. Highlights: In this retrospective study, we identified pre-operative risk factors for conversion to open in laparoscopic appendectomy. The conversion from laparoscopic to open appendectomy cohort had worse outcomes as compared to the primary open cohort. These pre-operative factors could help select for patients who may benefit from primary open appendectomy.